The Nexus Between Economic Freedom and Tourist Arrivals: Evidence from Mediterranean Countries - Oğuz Öcal; Buket Altınöz; Alper Aslan (İstanbul İktisat Dergisi)
Mediterranean countries are indispensable places of tourism with their world-famous shores, wonderful climate and impressive historical places. The aim of this paper is to investigate the relationship between tourist arrivals and economic freedom indicators such as government integrity, tax burden, government spending, business freedom and trade freedom. For this purpose, the panel vector autoregression (PVAR) method was used for a Mediterranean countries sample covering the period from 1996 to 2016. The results of causality testing showed that the tourist arrivals have a bidirectional causality relationship with each explanatory variable, while the coefficient estimates showed that an increase in economic freedom indices affected tourist arrivals negatively in Mediterranean countries. That is, economic freedoms do not mean an advantage for tourists without supportive public policies for tourism. The test results suggest that policymakers should take into account the various aspects of the tourism sector, particularly natural resources and environmental factors, while making policies that increase economic freedom in Mediterranean countries.